Bulk Density Measurements of Small Solid Objects Using Laser Confocal Microscopy. Issue 1 (11th November 2016) - Kilmametov, Askar; Gröger, Roland; Hahn, Horst; Schimmel, Thomas; Walheim, Stefan
Abstract : In this study a novel approach for precise density measurement of samples with a small weight in the range of 1–3 mg is presented. A new kind of displacement method has been developed, by which a solid object is dropped into a semi‐confined cylindrical cavity, which is filled with a nonvolatile liquid, to determine the volume of the sample. Due to surface tension, the upper level of the liquid forms a spherical meniscus pinned at the circular contact line, which is limited by a printed hydrophobic self‐assembled monolayer. Monitoring of the liquid level is performed by confocal laser microscopy with µm‐resolution. A straightforward procedure is developed to build‐up a mass/volume linear dependence. This enables to determine the density of small solids with an accuracy of ≤0.5%. The method appears to be very sensitive to open and closed porosity. Applying a vacuum of 20 mbar to the already immersed samples allows to perform quantitative porosimetry on a rather limited amount of material of only ≈0.25 µL. This corresponds to about 2–5 mg for most metals, 1–2 mg for most ceramics, or even only 0.25–1 mg for organic materials. Abstract : A novel approach to measure the density of small samples uses the geometrically well‐defined shape of a liquid meniscus. Using laser confocal microscopy the volume and therefore the density of samples of only a few mg dropped into a liquid can be determined with an accuracy of ≤0.5%.